EVALUATION OF TREATMENT OF PATIENTS WITH ACUTE MYOCARDIAL INFARCTION BEFORE REFERENCE EVENT AND BEFORE DISCHARGE FROM THE HOSPITAL: REGISTER DATA (KHABAROVSK CITY). PART 2 - L. N. Malay; S. Yu. Martsevich; L. V. Solokhina; Y. M. Bukhonkina; K. E. Poshatayev; N. B. Garayeva; A. Ya. Letskin (Рациональная фармакотерапия в кардиологии)
Aim. To study a treatment of patients with acute  myocardial infarction (AMI) before  and during hospitalization in a Khabarovsk  hospital, which has an opportunity of primary percutaneous coronary  intervention (PCI), as well as hospital outcomes according to the AMI Register.Material and methods. 321 patients consecutively hospitalized in the Khabarovsk  Regional Vascular Center were included into AMI Register: 177 patients with ST-segment elevation AMI (STEMI; 55.1%); 135 patients non-ST-segment elevation AMI (non-STEMI; 42.1%); 9 patients with early recurrence of AMI and early post-infarction stenocardia (2.8%).Results. Before reference AMI a frequency of administration of statins was 13.7%, angiotensin-renin blockers – 29.3%, acetylsalicylic acid – 28.7%, beta-blocker – 25%. Among patients with atrial fibrillation only 7 ones (17%) were treated with oral anticoagulants.        141 patients (79.6%) with STEMI underwent PCI procedure: primary PCI – 82.3% and delayed PCI – 17.7%. PCI with coronary  stenting was performed  in 86.5% of patients with STEMI. Frequency  of PCI in non-STEMI patients was 42%: primary PCI – 43.9%, delayed PCI – 56.1%, PCI with coronary stenting – 43.9%. Gender and age of the patients did not influence the choice of tactics of revascularization in STEMI and non-STEMI (PCI(+), PCI(-), PCI with coronary  stenting) (p<0.05).Medication in hospital: double antithrombotic therapy (DATT) was prescribed in 86.9% of patients; direct anticoagulants – in 91.2%, statins – in 97.2%, beta-blockers – in 88.5%; renin-angiotensin-aldosterone system inhibitors – in 90.6%. A total lethality in STEMI was 15.2%, and in non-STEMI – 1.5%. Lethality in PCI-negative patients with STEMI was higher than  this in patients with non-STEMI (p<0.001). In STEMI patients lethality was 3.3  times lower in PCI-positive patients in comparison with PCI-negative patients.Conclusion. AMI Register demonstrated that before reference AMI very few patients were covered with modern medicines influencing prognosis. AMI hospital treatment in Khabarovsk Regional Vascular Center was characterized by a high rate of primary PCI, DATT, enoxaparin, and high-dose statin therapy.